Breus' Mole Associated with Hereditary Thrombophilia in A Teenage Girl - Suna Özdemir; Osman Balcı; Ali Haydar Kantarcı; Tuba Koyuncu; Cavide Sönmez (Medical Network, 2011)
Breus' mole is a rare event and it is most often found in the placenta of stillborn fetuses. It may occur in patients with disorders of circulation, complex heart disease, hypertension, diabetes and anticoagulation therapy. A 17 year old women with no previous gravida, was admitted to our clinic with intermittent vaginal bleeding and lower abdominal pain after 2 months amenorrhea. On admission, her general condition was normal and biochemical profiles were within normal ranges. Ultrasonography showed an enlarged uterus with hyper/hypoechogenic vesicular areas. Serum β-human chorionic gonadotropin (HCG) was tested as 33096 U/ml. Suction curettage under was performed due to the diagnosis of molar pregnancy. However, histology of the material was reported as Breus' mole. There was no evidence for complete or partial hydatidiform mole. In the genetic examination of the material, no chromosomal abnormality was detected. Homozygous mutation on factor V leiden gene was determined in the patient. Breus' mole should be considered in differential diagnosis of early gestational disorders, and the patients with Breus'mole should be tested for hereditary thrombophilia.